Basilar Artery Thrombosis Diagnosed by MR Imaging - Martinez, Hector R.; Elizondo, Guillermo; Herrera, Jaime; Marfil, Alejandro; Ancer, Jesus; Gonzalez, Jorge; Rangel-Guerra, Ricardo; Todd, Luis E. (American Journal of Neuroradiology, 1989)
300 Multiple ChoicesThis is a pdf-only article and there is no markup to show you.full-text.pdf